Pengelolaan Sarana dan Prasarana Pendidikan dalam Meningkatkan Mutu Pembelajaran Siswa di Madrasah Aliyah Darul Lughah Wal Karomah - Kurniana, Nela; Wahab, Abd Aziz; Badruddin, M. Fuad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Management of Educational Facilities and Infrastructure in Improving the Quality of Student Learning at Madrasah Aliyah Darul Lughah Wal Karomah